Assessment of communication skills in MBBS interns with objective structured video examination (OSVE) - Megha Luthra; Puneet Ohri; Utkarsh Sharma; Ashwani Sharma; Soumya Mohanty; Sonam Maheshwari (Wolters Kluwer Medknow Publications, 2023)
Background: Medical graduates enter work force with substantial knowledge but are they prepared for practice in diverse settings? To train medical interns in communication skills using Demonstration Observation Assistance and Performance (DOAP) and to assess communication skills in medical interns using objective structured video examination (OSVE). Methods and Materials: DOAP sessions of all 27 interns posted in Community Medicine and Pediatrics departments during the duration of the study were conducted in six clinical scenarios followed by two OSVEs. Methods and Material: Interns performed selected activity independently twice for assessments. Videos submitted by interns were assessed by Gap Kalamazoo assessment forms (OSVE). Data analysis was done by appropriate methods. Percentages and proportions and calculation of median scores with interquartile ranges. Results: Seventy one point four percent of faculty and 96.3% of interns were satisfied with module implementation. More than = 57.8% marks were scored by 94.45% interns in self-assessment and faculty assessment and by 100% interns in patient assessment. Median scores of all second assessments were higher. Conclusions: DOAP method is good for training of interns in communication skills. OSVE may be an appropriate assessment tool as it leads to progression in learning.